Immunohistochemical markers in renal tumors and findings in non-tumoral renal parenchyma - (:unkn) unknown (My University, 2010)
Objective: Renal epithelial cells comprise distinct pathological and physiological differences. Renal epithelial neoplasms derived from these cells may show overlapping morphological features, and differential diagnosis requiring the use of ancillary methods. The purpose of this study was to determine the diagnostic utility of the immunohistochemical expression patterns of a wide range of markers in renal epithelial cells. Material and Method: Normal renal cortical parenchyma and renal pelvis were immunostained for cytokeratin (CK) subtypes (CK7, CK19, CK34βE12), vimentin, RCCMa, CD10, CD117, AMACR, WT-1, EMA and p63. The immunohistochemical expression patterns were examined in 10 cases. Results: Although there is some overlap, subtypes of epithelial cells showed distinctive CK and CD expression profiles. Proximal tubular cells showed CD10, RCCMa, AMACR expression. Distal tubular cells and collecting ducts showed CK7, CK19 and EMA expression. Urothelial cells showed CK7, CK19, CK34βE12, and p63 expression. CD117 and vimentin selectively stained intermittently in some cells lining the tubules. Endothelial cells and visceral epithelial cells stained with WT-1. Glomerular epithelial cells stained with CD10, but focal and intermittent staining with AMACR, CK7, CK 19, and RCCMa was found in parietal cells. Conclusion: In conclusion, a panel of cytokeratins, CDs and other markers are helpful in distinguishing epithelial cells and urothelial cells. The expression patterns of these markers may be helpful in the differential diagnosis of epithelial neoplasms.